Adapting to post-COVID19 research in Parkinson's disease: Lessons from a multinational experience. (January 2021) - Tan, Eng-King; Albanese, Alberto; Chaudhuri, KRay; Lim, Shen-Yang; Oey, Nicodemus Edrick; Shan Chan, Christine Hui; Wu, Yun-Cheng; Jeon, Beomseok; Truong, Daniel; Poewe, Werner; Pal, Pramod Kumar; Tan, Louis; et al.
Highlights: COVID-19 has significant impact on PD research and education activities. Country-specific restrictions may pose challenges to PD research and require careful adaptations. Neurological Symptoms of COVID-19 may overlap with PD.